Hakikat Agama Dalam Pembentukan Karakter Anak Usia Dini - Nurma Nurma; Maemonah Maemonah (UIN Sultan Maulana Hasanudin Banten, 2022)
Religion has a big influence in shaping the character of the nation's children. Children's character can be formed from an early age through a continuous education process. The direction of education is to humanize humans. Humans cannot be separated from education as well as education, the two are interconnected, will function if they are not separated. Educational actions are directed at humans to develop the potentials that already exist in them, namely the potential to do good. Teaching to children includes the values ​​of religious teachings, namely the values ​​of aqidah, values ​​of worship, moral values. The purpose of practicing religious values ​​is to form a positive character from an early age. Achievement of teaching can be implemented using various learning methods. The current phenomenon of the role of educators in inculcating teaching values ​​is still low, this can be seen where children are still not able to apply the values ​​of religious teachings in behavior. True moral investment must start early as the initial formation of future capital.